DIAGNOSTIC ACCURACY OF RIPASA SCORE - Akbar, Ismail; Shehzad, Jawad Ahmed; Ali, Shoaib (Journal of Ayub Medical College Abbottabad, 2019)
Background: Acute appendicitis is one of the most common acute surgical emergencies on emergency room floor and timely diagnosis of the condition is of utmost importance. Multiple diagnostic Score exist to help in the clinical diagnosis; among Which RIPASA is a recent introduction. Methods: The study was carried out Ayub Teaching hospital of Abbottabad from Sept-2017 to Feb-2018, Department of General Surgery. The ultimate decision to perform surgery was not guided by the scores and the surgeon's decision was the final word, and specimens were sent afterward for histopathology. The results compiled and entered into SPSS 20. Results: Out of the 308, 288 patients underwent surgery for AP, 165 (57.3%) were male and 123 (42.7%) were female, 252 (87.5%) had positive histopathology report and 36 (12.5%) had a negative report, with resultant negative appendectomy rate of 12.5% well below the average. 26 (9.02%) had a perforated appendix and 8 (2.8%) had post-op wound infection. The sensitivity of RIPASA score at a cut-off value of 7.5 was 98.02%, with specificity of 75%, and Positive Predictive Value of 96.48%, and Negative Predictive Value of 84.7%. Compared to Alvarado's Score Sensitivity and Specificity of 53% and 75% respectively. Conclusion: On the balance the RIPASA Score detects early preventing from dreadful complication and in turn have low specificity giving way to a slightly higher negative appendectomy rate with the consequent morbidity and mortality of unnecessary surgery. Still RIPASA Score outperforms the Alvarado and Modified Alvarado Score. Keywords: Acute Appendicitis; RIPASA Score; South-Asian Population